2021
DOI: 10.1016/j.asmr.2020.07.023
|View full text |Cite
|
Sign up to set email alerts
|

Return-to-Play and Rehabilitation Protocols Following Isolated Meniscal Repair—A Systematic Review

Abstract: Purpose To systematically review the literature and assess the reported rehabilitation protocols, return-to-play guidelines, and reported rates of return-to-play after meniscal repair. Methods MEDLINE, EMBASE, and the Cochrane Library were searched according to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines to identify studies on meniscal repair. Studies were included if return-to-play data and/or rehabilitation protocols were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 36 publications
0
10
0
Order By: Relevance
“…Meniscal repair is largely performed in young and active patients including elite and professional athletes, but only a few studies looked at the RTS after meniscal repairs using a sport-specific approach [33][34][35]. Only six studies specifically evaluated RTS in either mixed-level or professional athletes after isolated meniscal suture [31,[36][37][38][39][40].…”
Section: Return To Sport (Rts)mentioning
confidence: 99%
“…Meniscal repair is largely performed in young and active patients including elite and professional athletes, but only a few studies looked at the RTS after meniscal repairs using a sport-specific approach [33][34][35]. Only six studies specifically evaluated RTS in either mixed-level or professional athletes after isolated meniscal suture [31,[36][37][38][39][40].…”
Section: Return To Sport (Rts)mentioning
confidence: 99%
“…Pogorelic et al [50] did not specify their rehabilitation protocol. A recent systematic review analysed the rehabilitation protocol in 88 studies after meniscal repair [17]. In two‐thirds of the included studies, partial weight bearing was allowed within the first week.…”
Section: Discussionmentioning
confidence: 99%
“…26 , 27 Eberbach et al 26 in their systematic review reporting sport-specific outcomes after isolated meniscal repair, also reported that similarly successful outcomes were observed in both recreational and professional level athletes. Fried et al 28 in their systematic study on RTP and rehabilitation after isolated meniscal repairs, found a RTP rate ranging from 71.2% to 100%, while 53.9% to 92.6% returned to the preinjury level. Additionally, they found that 44% had returned to play within 4 months after surgery and up to 97% RTP within 6 months postoperatively.…”
Section: Discussionmentioning
confidence: 99%